ANALISIS YURIDIS PERTIMBANGAN HAKIM ATAS SENGKETA KEPEMILIKAN MEREK ASING TERKENAL BERDASARKAN PUTUSAN MAHKAMAH AGUNG 2018-2020 - Ridha Faulika Irtiyah (Jurnal Abdi Ilmu, 2021)
Pilgrimage of fame to well-known foreign brands is common in Indonesia and there is still insufficient protection of the rights of well-known foreign brands. Based on this description, the following problems are formulated: 1. What are the things that cause disputes over the ownership rights of well-known foreign brands in Indonesia? 2. What are the criteria for proving ownership of a well-known foreign mark in the Supreme Court's decision from 2018-2020? 3. How is the application of law in legal protection for well-known foreign brand owners in Indonesia? The type of research used in completing the thesis is normative juridical research, namely an effort to study the legal rules as written. The data collection technique was carried out through library research, which was obtained through document studies and collecting the decisions of the Supreme Court of the Republic of Indonesia. The results of the study show that there are 2 (two) things that cause ownership rights disputes for well-known foreign brands: 1. Bad faith in the registration of well-known marks, namely business actors who register brands and imitate brands that have a high selling value in the market, 2. Bad faith both in the famous trademark license agreement, that is, if the parties making the famous trademark license agreement terminate the agreement unilaterally, besides that the use of a new mark by the licensee is detrimental to the owner of a well-known foreign mark. The criteria for proving ownership of a well-known foreign mark in the 2018-2020 Supreme Court Decision, the Panel of Judges to determine the criteria for a dominant well-known mark using Article 21 paragraph (1) letter b of the Trademark Law and Geographical Indications and Article 18 paragraph (3) Regulation of the Minister of Law and Human Rights No. . 67 of 2016. However, there are several judges who made a mistake in deciding their case and did not apply the law using the articles above, even though these articles were already in effect when the case of a well-known foreign brand was in court. The Application of Law in the Legal Protection of Famous Foreign Marks The Supreme Court Decision From 2018-2020 uses Law Number 20 of 2016 concerning Marks and Geographical Indications Article 20, Article 21, Article 74 paragraph (1), Article 76 paragraph (1), Article 77 paragraph (1) and Article 181 of HIR in the form of cancellation of trademark registration, deletion of marks, and payment of court fees charged to the losing party.